Artificial intelligence in clinical endoscopy: Insights in the field of videomics - Paderno, Alberto; Gennarini, Francesca; Sordi, Alessandra; Montenegro, Claudia; Lancini, Davide; Villani, Francesca Pia; Moccia, Sara; Piazza, Cesare (Frontiers in Surgery, 2022)
Artificial intelligence is being increasingly seen as a useful tool in medicine. Specifically, these technologies have the objective to extract insights from complex datasets that cannot easily be analyzed by conventional statistical methods. While promising results have been obtained for various -omics datasets, radiological images, and histopathologic slides, analysis of videoendoscopic images still represents a major challenge. In this context, videomics represents a burgeoning field wherein several methods of computer vision are systematically used to organize unstructured data from videoframes obtained during diagnostic videoendoscopy. Recent studies have focused on five broad tasks with increasing complexity: quality assessment of endoscopic images, classification of pathologic and non-pathologic frames, detection of lesions inside frames, segmentation of pathologic lesions, and in-depth characterization of neoplastic lesions. Herein, we present a broad overview of the field, with a focus on conceptual key points and future perspectives.